Бандурне мистецтво Волині: від аматорства до професіоналізму - Чернецька, Наталія Григорівна; Chernetska, Nataliia H. (Рівненський державний гуманітарний університет, 2015)
Досліджено шляхи професіоналізації бандурного мистецтва Волині другої пол. ХХ – початку ХХІ ст.; наведено факти вдосконалення інструментарію; висвітлено творчість окремих персоналій та педагогічні досягнення провідних фахівців; окреслено просвітницьку роль концертної діяльності бандуристів.The article reviews ways of professional development in bandore performing art of Volyn in the latter half of the twentieth century up to the early 21st century, gives the facts of instrument improvement, highlights creative work of some musicians and pedagogical achievements of leading specialists, outlines the educational role of bandore players’ concerts. After World War II the music culture of Volyn was developing mainly as amateur artand was under control of competent authorities (the Communist party’s watchdogs) and became an important means of communist education. However, in Lutsk in 1944 Yu.Bartoshevskiyi started up a course of study specializing in bandore at Lutsk Music School, later the bandore band was arranged (musical director – A.Vashchenko), the bandore workshop was run by expert V.Tuzichenko. The next logical step was made with launching a new study course specializing in bandore in Lutsk Music Professional School in 1959. Its graduates I.Skira, Yu.Bokovyi, T.Tkach made the bandore-specializing study professional. It was possible to get professional music education at children’s music schools in the region as well as at Lutsk College of Art and Lutsk Teachers’ Training College. It gave the chance to set up various bandore bands that promoted the bandore art at regional and republican levels. Another indicator of professional development in the bandore education was starting a bandore-specializing course at Lutsk Teachers’ Training Institute in 1988 and it resulted in the instrument introduction into school activities. The forward step in bandore performing art was arranging music festivals and contests of regional and all-Ukrainian levels in Lutsk, these events are of great importance for stirring up the bandore education and performing, making the instrument popular among the youth. Thus, the distinguishing features of professional growth in bandore performing art of Volyn in the latter half of the twentieth century up to the early 21st century include the following activities such as: instrument improvement, molding a three-level education (a music school, a college and an institute), bandore players’ professional training, arranging concerts and other education activities, introducing bandore into school activities, holding musical contests, revealing students’ creative potential, promoting the bandore art via a series of art projects. Thus, bandore performing art of Volyn in the latter half of the twentieth century up to the early 21st century corresponded to the stages of general art transformation. Creative growth of amateur bands, instrument improvement, and professional development of bandore training were of special significance and became evidence of regional art and culture progress.
Bandore Performing Art of Volyn: from Amateur to Professional Manner
Keywords: бандурне мистецтво; бандурист; концертна діяльність; ансамблеве виконавство; бандурний репертуар; bandore art; bandore player; concert activity; ensemble performance; bandore repertoire